1998
DOI: 10.1128/cdli.5.3.335-340.1998
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Gene Expression in Normal Human Lymphocytes in Response to Stimulation

Abstract: Sequential gene expression of two type 1 cytokines (interleukin 2 [IL-2] and gamma interferon), one type 2 cytokine (IL-10), two monokines (IL-6 and tumor necrosis factor alpha), and one cytokine receptor (IL-2 receptor [IL-2R]) in normal human peripheral blood mononuclear cells (PBMC) following in vitro stimulation was investigated by reverse transcription-PCR methods. Two stimuli were utilized: phytohemagglutinin (PHA), which acts on the CD2 molecule and T-cell receptors, and anti-CD3 monoclonal antibody, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 49 publications
6
22
0
2
Order By: Relevance
“…**P , 0.01 for vehicle + BFA compared with anti-CD3 + BFA. and IL6 and the anti-inflammatory IL10 by anti-CD3-stimulated PBMCs [37] further support the hypothesis that the delayed IL1F7 mRNA expression observed here originated from cells other than T cells.…”
Section: Discussionsupporting
confidence: 88%
“…**P , 0.01 for vehicle + BFA compared with anti-CD3 + BFA. and IL6 and the anti-inflammatory IL10 by anti-CD3-stimulated PBMCs [37] further support the hypothesis that the delayed IL1F7 mRNA expression observed here originated from cells other than T cells.…”
Section: Discussionsupporting
confidence: 88%
“…We also observed that even unstimulated PBMCs expressed low levels of all cytokine transcripts studied. Our results are consistent with observations for IFN-c expression in unstimulated spleen cells (Iizawa et al 1992), IL-2 and IFN-c expression in rat resting T-cell clones (Zhao et al 1994), and IL-2, IFN-c, IL-6, IL-10 and TNF-a transcripts in unstimulated human PBMCs (Fan et al 1998). Beta actin expression was little affected by mitogenic stimulation of PBMCs at any point of time examined in both Zovawk and LWY pigs, thus serving as the reference gene (Facci et al 2011) in our real-time PCR assay.…”
Section: Discussionsupporting
confidence: 92%
“…Upon PBMCs activation, coordinated secretion of various cytokines control proliferation, differentiation, and function of cells and are crucial for regulation of immune response (Corry et al 1996;Fan et al 1998;Dar et al 2015). Our results depict significant increase in all the cytokines genes' expression assayed except IL-2, within 1 to 3 h of PHA-P stimulation.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Id‐specific mRNA gene expression was expressed as a ratio between the relative increase of a gene induced by the autologous Id compared with that of the isotype control (fold increase ratio). The expression of each gene was calculated in relation to unactivated cells after normalization against β‐actin (28, 29). An Id‐specific response was considered when the relative fold increase of a gene induced by the autologous Id was higher than the isotypic control.…”
Section: Methodsmentioning
confidence: 99%